Effects of data sources and biological criteria on length-at-maturity estimates and spawning periodicity of the commercially important Hawaiian snapper, Etelis coruscans - Reed, Erin M.; Brown-Peterson, Nancy J.; DeMartini, Edward E.; Andrews, Allen H. (Frontiers in Marine Science, 2023)
Reproductive characteristics of a fish stock provide important tools for assessing population health. Change in length-at-maturity (L50) is a potential indicator of exploited fish populations but when criteria for determining maturity classifications are inconsistent, it is difficult to accurately assess change over time and space. Etelis coruscans is a commercially important eteline snapper found throughout the Indo-Pacific, but its region-specific reproductive information in the main Hawaiian Islands (MHI) is sparse. The present study describes length-specific (fork length: FL) female reproductive characteristics of this deep water snapper in the context of a data-limited fishery. We explored the use of six maturity classification criteria based on a functionally mature (containing vitellogenic oocytes and capable of spawning within the season of collection) or physiologically mature (gonadotropin-dependent maturation initiation) designation combined with seasonality and inclusion of additional reproductive phases. Of these classifications, the largest and therefore most conservative estimate was for functional maturity during the spawning period, September-December (L50F = 65.8 cm). Progressively smaller L50 estimates occurred as we incorporated additional reproductive phases and seasonality, the smallest being for physiological maturity during the entire year (L50PY = 50.0 cm). Both functional and physiological maturity criteria are valid for estimating L50 but can yield drastically different parameter estimates based on the definition of mature or immature reproductive phases. Fish that are relatively slow growing, late to mature, and whose fisheries encompass a wide size range, such as E. coruscans, may be more subject to unreliability in the development of their reproductive indicators (length-at-maturity and spawning period) when inconsistent maturity classification criteria are executed over time. We discuss the reproductive characteristics of E. coruscans in the MHI, the use of alternative maturity classification criteria in L50 estimation, the impact on resultant parameters estimates, and the life history implications for the future fishery.